Hass Avocado Inclusion in a Weight-Loss Diet Supported Weight Loss and Altered Gut Microbiota: A 12-Week Randomized, Parallel-Controlled Trial. Issue 8 (12th June 2019) - Henning, Susanne M; Yang, Jieping; Woo, Shih Lung; Lee, Ru-Po; Huang, Jianjun; Rasmusen, Anna; Carpenter, Catherine L; Thames, Gail; Gilbuena, Irene; Tseng, Chi-Hong; Heber, David; Li, Zhaoping
ABSTRACT: Background: Avocados contain fiber, lutein, and vitamin E, and they are a rich source of MUFAs. The effect of including an avocado daily as part of a hypocaloric weight-loss diet on weight loss is not known. Objective: The aim of this study was to determine the effect of daily avocado consumption as part of a hypocaloric diet on weight loss, body composition, satiety, biomarkers of inflammation, and intestinal microbiota composition. Methods: In this randomized, parallel-controlled, open-label, 2-arm intervention study, 51 healthy overweight/obese women and men were assigned to a hypocaloric diet with 1 Hass avocado daily (AVO; n  = 24) or a hypocaloric diet (CTRL; n  = 27) without daily avocado for 12 wk. Serum markers and intestinal microbiota were analyzed at baseline and week 12. Results: Both groups experienced significant weight loss, decrease in BMI (in kg/m 2 ), total body fat, and visceral adipose tissue, respectively (AVO: −2.3 ± 2 kg, −0.8 ± 0.8, −1.1% ± 2%, and −81.2 ± 118 g; CTRL: −2.6 ± 3.6 kg, −0.9 ± 1, −1.5% ± 2%, and −87.4 ± 216 g). We observed a significant decrease in serum glucose over time in the control group compared with the AVO group. There was no change between the groups in serum triglyceride, but a significant decrease from baseline to 12 wk was observed in the AVO group. Serum hepatic growth factor (HGF) and relative proportion of bacterial phyla (Firmicutes and Bacteroidetes), family (Bacteroidaceae and Erysipelotrichaceae), and genus ( Bacteroides, Clostridium, Methanosphaera, and Candidatus Soleaferrea ) were significantly altered in the AVO group compared with the CTRL group. A trend to decrease in serum inflammatory factors IL-1β ( P  = 0.07) and C-reactive protein ( P  = 0.074) was observed in the AVO group compared with CTRL. Conclusions: Daily Hass avocado consumption as part of a hypocaloric diet supported weight loss, a decrease in serum HGF, and an increase in the abundance of bacteria involved in plant polysaccharide fermentation. This trial was registered at clinicaltrials.gov as NCT02953158.